What do care home managers believe constitutes an ‘assessment for frailty’ of care home residents in North-West London? A survey - David Sunkersing (BMC Geriatrics, 2019)
Abstract Background Frail individuals are at risk of significant clinical deterioration if their frailty is not identified and managed appropriately. Research suggests that any interaction between an older person and a health or social care professional should include an assessment for frailty. Many older care home residents are frail when admitted, but we have little knowledge of whether or how this is assessed. The aim of this paper is to understand and establish the characteristics of the reported ‘assessments for frailty’ used in care homes with nursing (nursing homes) across North-West London. This will help understand what an ‘assessment for frailty’ of care home residents mean in practice in North-West London. Methods Telephone contact was made with every Care Quality Commission (CQC) (independent regulator of health and adult social care in England) regulated nursing home across North-West London [n = 87]. An online survey was sent to all that expressed interest [n = 73]. The survey was developed through conversations with healthcare professionals, based on literature and tested with academics and clinicians. Survey responses were analysed using descriptive statistics. The Mann-Whitney U test was used for statistical analyses. Results 24/73 nursing homes completed the survey (33%). Differences in the characteristics of reported ‘assessments for frailty’ across nursing homes were evident. Variation in high level domains assessed (physical, social, mental and environmental) was observed. Nurses were the most common professional group completing assessments for frailty, with documentation and storage being predominantly paper based. A statistically significant difference between the number of assessments used in corporate chain owned nursing homes (3.9) versus independently owned nursing homes (2.1) was observed (U = 21, p = .005). Conclusions Great variation existed in the characteristics of reported ‘assessments for frailty’ in nursing homes. Our study suggests that not all physical, social, mental and environmental domains of frailty are routinely assessed: it appears that frailty is still primarily viewed only in terms of physical health. The consequences of this could be severe for patients, staff and healthcare settings. Research illustrates that frailty is a broad, multifactorial health state and, as such, an overall ‘assessment for frailty’ should reflect this.